Waiting for a diagnosis in Rubinstein–Taybi: The journey from "ignorance is bliss" to the value of "a label". Issue 1 (16th October 2020) - Withers, Chelsea M.; Fleming, Jane; Wallingford, Courtney K.; Gabbett, Michael T.; Peterson, Madelyn; Humphreys, Linda; McInerney‐Leo, Aideen
Abstract: The journey to receiving a diagnosis for rare genetic disease can be long and emotionally impactful. This study describes parental experiences of receiving their child's diagnosis of Rubinstein–Taybi syndrome (RTS), a rare genetic condition characterized by growth and developmental delay together with dysmorphic features. Parents from the RTS Australia support group participated in qualitative, semi‐structured phone interviews, which were transcribed verbatim and thematically analyzed. Questions focused on psychosocial challenges and benefits pre and post‐diagnosis. Ten mothers and three fathers participated, with the mean age of diagnosis being 8 months. Parents reported positive psychological effects from a slight delay in diagnosis, and negative effects from an extended diagnostic delay, suggesting the ideal time for a parent to receive a diagnosis lies in the post attachment stage, prior to the development of significant parental concerns. This stage would vary depending on condition severity. Parents desired a diagnosis to reduce uncertainty; however, uncertainty remained post diagnosis, and shifted its focus from broadly encompassing etiology and prognosis, to specifically focusing on concerns regarding severity within the spectrum. Perceived benefits of a diagnosis mainly centered on the provision of a label. Parents articulated that a label increased social acceptance, enhanced coping, promoted communication, and improved access to medical, financial, and support services. This study provides insights into the experience of families prior to and following receipt of a diagnosis. It also highlights the possibility of an optimal time window to receive a diagnosis; in which bonding is maximized and parental distress is minimized.